Analysis of The Importance of Distributing Social Assistance to The Ministry of Social Affairs Through Social Media Twitter - Nur Hidayatullah; Suswanta Suswanta (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Currently, Twitter social media performs a necessary function by the Ministry of Social Affairs of the Republic of Indonesia in encouraging information sharing. So that the presence of social media accounts Twitter @KemensosRI is the item of this research observation. This learns about aims to spotlight the overall performance and centre of attention of the Ministry of Social Affairs of the Republic of Indonesia in the distribution of social assistance in Indonesia. This study uses qualitative research with the help of Nvivo 12 plus software. Then, to answer this question, we gathered data from the Twitter social media account @KemensosRI from March 2021 to January 2023. The levels of records evaluation have been (1) shooting data, (2) information classification information, (3) coding information (4) results. This study's findings point out that the distribution of social assistance by using the Ministry of Social Affairs solely represents the elements of the poor or underprivileged, disaster management, and people with disabilities. This means that the Government only focuses on that field. The mechanism for distributing social assistance has been running effectively and efficiently so that it is right on target for social assistance recipients